Dual effects of GABAAR agonist anesthetics in neurodevelopment and vulnerable brains: From neurotoxic to therapeutic effects - Dihan Lu; Wen Zhang; Keyu Chen; Xia Feng (Neural Regeneration Research)
Debates regarding the specific effects of general anesthesia on developing brains have persisted for over 30 years. A consensus has been reached that prolonged, repeated, high-dose exposure to anesthetics is associated with a higher incidence of deficits in behavior and executive function, while single exposure has a relatively minor effect on long-term neurological function. In this review, we summarize the dose-dependent neuroprotective or neurotoxic effects of gamma-aminobutyric acid type A receptor agonists, a representative group of sedatives, on developing brains or central nervous system diseases. Most preclinical research indicates that anesthetics have neurotoxic effects on the developing brain through various signal pathways. However, recent studies on low-dose anesthetics suggest that they may promote neurodevelopment during this critical period. These findings are incomprehensible for the general “dose-effect” principles of pharmacological research, which has attracted researchers’ interest and led to the following questions: What is the threshold for the dual effects exerted by anesthetics such as propofol and sevoflurane on the developing brain? To what extent can their protective effects be maximized? What are the underlying mechanisms involved in these effects? Consequently, this issue has essentially become a “mathematical problem.” After summarizing the dose-dependent effects of gamma-aminobutyric acid type A receptor agonist sedatives in both the developing brain and the brains of patients with central nervous system diseases, we believe that all such anesthetics exhibit specific threshold effects unique to each drug. These effects range from neuroprotection to neurotoxicity, depending on different brain functional states. However, the exact values of the specific thresholds for different drugs in various brain states, as well as the underlying mechanisms explaining why these thresholds exist, remain unclear. Further in-depth exploration of these issues could significantly enhance the therapeutic translational value of these anesthetics.